Perdamaian dan Tantangannya; Reintegrasi, Otonomi Khusus, dan Dominasi Elit Pascakonflik Aceh - Saiful Asra; Mohammad Agus Yusoff; Mursyidin Mursyidin; Afrizal Tjoetra; Lilis Sariyanti (Jurnal Community, 2025)
The Aceh conflict, one of the longest separatist struggles in Indonesia, lasted for nearly three decades and caused severe social, political, and economic consequences. The turning point occurred after the 2004 tsunami, which opened the door for peace negotiations between the Government of Indonesia and the Free Aceh Movement (GAM). This study aims to analyze the political transformation of GAM following the signing of the 2005 Helsinki Memorandum of Understanding (MoU), focusing on the dynamics of demobilization, reintegration, and democratization in Aceh. Using a historical approach and library research, data were collected from primary sources such as official documents and archival records, as well as secondary sources including books, journals, and reports. The findings show that the MoU Helsinki not only ended armed conflict but also initiated significant political transformation by allowing the establishment of local political parties and expanding Aceh’s autonomy. However, challenges persist in reintegration programs, governance of special autonomy funds, and center local relations. While GAM successfully transitioned from armed resistance to formal politics, issues of social justice, economic inequality, and elite dominance continue to hinder sustainable peace. This study highlights that Aceh’s experience offers important lessons for conflict transformation and peacebuilding in post-conflict societies.